Design of Photography Center in Pekanbaru with Hi-Tech Architecture Approach - Mazairi, M. Nuril; Husaini, Muhd. Arief Al; Firzal, Yohannes (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2024)
Photography center is used for photography activities as a meeting place for photographers, professional or amateur, and art lovers. Pekanbaru is experiencing a growing trend of photography enthusiasts with the growth of photography communities and the use of photography media in various activities. Studio facilities with existing equipment allow for intensive photography practice and learning. The need for the construction of a Photography Center in Pekanbaru is due to the absence of a building as a place for the photography community to share and collaborate. The purpose of this design is to create a photography center building that reflects technological advances and provides a visual experience. The method used is descriptive qualitative by conducting observations and interviews in data collection. The design of the Photography Center is designed with a visual aesthetic design approach and responds to today's needs.